The genus Keilbachia Mohrig (Diptera: Sciaridae) in a biodiversity hot spot: new sympatric species from Kambaiti, Burma - Vilkamaa, Pekka; Komarova, Lyudmila A.; Hippa, Heikki (Zootaxa, 2006)
Eight new, strictly sympatric species of the genus Keilbachia Mohrig, 1987, from Burma (Myanmar) are described and illustrated: Keilbachia aculeata, K. apprima, K. arcuata, K. arrecta, K. demissa, K. mira, K. scutica, and K. tenuicula. Keilbachia flagrispina Mohrig is redescribed on the basis of Burmese specimens. A key to all currently known species of Keilbachia is presented.